Nutritional composition, antioxidant activity and anticancer potential of Syzygium cumini (L.) and Syzygium malaccense (L.) fruits (Research, Society and Development, 2021)
Intending to highlight new fruits with nutraceutical potential, the present work reports the nutritional and antioxidant content of Syzygium cumini (L.) Skeels (S. cumini) and Syzygium malaccense (L.) Merr. & LM Perry (S. malaccense), and evaluates the anticancer potential against CP-H460 (lung carcinoma line) and its functionality over HEK-293 (healthy embryonic kidney line), two human cells. For this, the physical-chemical characterization of the lyophilized fruits was carried out, and the content of total phenolic compounds (Folin-Ciocalteau) and the antioxidant potential (DPPH, FRAP, and ORAC) was determined. For anticancer activity, aqueous extracts were prepared and evaluated using the MTT (3-[4,5-dimethyl-triazol-2-yl]-2,5-diphenyltetrazolium) assay for periods of 20 hours. These two species are rich in dietary fibers, mainly insoluble fibers, and are sources of natural compounds and antioxidants, which possibly explain the protective potential against cancer cells. Thus, it is expected, as two source fruits, results obtained (p